Pengaruh Penambahan Fiber Baja Seling dengan Volume Fraction 0,4%, 0,6% dan 0,8% terhadap Kuat Tekan dan Kuat Tarik Lentur pada Beton Mutu Normal. - Marvin, Tiffany; Purwanto, Eddy; Irianti, Laksmi (Universitas Lampung, 2016)
This research was conducted to study and determine the influence of steel sling fiber 0,4%, 0,6% and 0,8% volume fraction of compressive strength and flexural strength on normal quality concrete. This study used an experimental method in the Laboratory of Material and Construction Engineering Faculty, University of Lampung. The compressive strength test specimen is a 30 cm height and 15 cm diameter cylinder and the flexural strength test specimen is a 40 cm length, 10 cm width and 10 cm height beam. The compressive strength and flexural strength test of normal quality concrete with 0,4%, 0,6% and 0,8% volume fraction held after 14 and 28 days. The maximum compressive strength and flexural strength value are at 0,6% volume fraction and decrease at 0,8% volume fraction. The maximum compressive strength is 27,5537 MPa at 0,6% volume fraction and the optimum value from polynomial trendline chart is 27,6028 MPa at 0,5754% volume fraction. The maximum flexural strength is 5,6899 MPa at 0,6% volume fraction and the optimum value from polynomial trendline chart is 5,7163 MPa at 0,5687% volume fraction. The steel sling fiber didn’t affect a high increase of the compressive strength, but this steel sling fiber had a high flexural strength which is 1733,46 MPa, so it affected a significant increase of the flexural strength test.Keywords : compressive strength, flexural strength, fiber concrete, steel sling fiber